Look at More : a Proven Approach to Innovation, Growth, and Change. - Stefanovich, Andy (John Wiley & Sons, 2011)
Why does real innovation elude so many companies, including the biggest corporations with the best technical processes, the cheapest resources, and a Chief Innovation Officer in place to implement corporate-wide innovation strategies? The problem, in all these cases, is that they are lacking inspiration. Not to be confused with the burst of energy that sometimes occurs after reports of amplified quarterly earnings or the arrival of a charismatic new leader (both of those are real but tend to be short term), inspiration -- as defined and outlined in this book - is a discipline. It is a systemat.